Quantitative comparison of different fluorescent protein couples for fast FRET-FLIM acquisition. - Padilla-Parra, S; Audugé, N; Lalucque, H; Mevel, J; Coppey-Moisan, M; Tramier, M (2009)
The fluorescent-protein based fluorescence resonance energy transfer (FRET) approach is a powerful method for quantifying protein-protein interactions in living cells, especially when combined with fluorescence lifetime imaging microscopy (FLIM). To compare the performance of different FRET couples for FRET-FLIM experiments, we first tested enhanced green fluorescent protein (EGFP) linked to different red acceptors (mRFP1-EGFP, mStrawberry-EGFP, HaloTag (TMR)-EGFP, and mCherry-EGFP). We obtained a fraction of donor engaged in FRET (f(D)) that was far from the ideal case of one, using different mathematical models assuming a double species model (i.e., discrete double exponential fixing the donor lifetime and double exponential stretched for the FRET lifetime). We show that the relatively low f(D) percentages obtained with these models may be due to spectroscopic heterogeneity of the acceptor population, which is partially caused by different maturation rates for the donor and the acceptor. In an attempt to improve the amount of donor protein engaged in FRET, we tested mTFP1 as a donor coupled to mOrange and EYFP, respectively. mTFP1 turned out to be at least as good as EGFP for donor FRET-FLIM experiments because 1), its lifetime remained constant during light-induced fluorescent changes; 2), its fluorescence decay profile was best fitted with a single exponential model; and 3), no photoconversion was detected. The f(D) value when combined with EYFP as an acceptor was the highest of all tandems tested (0.7). Moreover, in the context of fast acquisitions, we obtained a minimal f(D) (mf(D)) for mTFP1-EYFP that was almost two times greater than that for mCherry-EGFP (0.65 vs. 0.35). Finally, we compared EGFP and mTFP1 in a biological situation in which the fusion proteins were highly immobile, and EGFP and mTFP1 were linked to the histone H4 (EGFP-H4 and mTFP1-H4) in fast FLIM acquisitions. In this particular case, the fluorescence intensity was more stable for EGFP-H4 than for mTFP1-H4. Nevertheless, we show that mTFP1/EYFP stands alone as the best FRET-FLIM couple in terms of f(D) analysis.